A ferroelectric optical cathode based on lithium-air battery and a preparation method thereof

By using a ferroelectric photocatalyst layer with directional space charge separation in lithium air batteries, combined with conductive carbon and modified binder, the problem of poor electrochemical performance and stability of lithium air batteries is solved, and the energy conversion efficiency and cycle life are improved.

CN118919740BActive Publication Date: 2024-12-20JIANGSU HI BATTERY ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411406963.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-20
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The electrochemical performance of existing lithium air batteries has not yet met expectations, the catalyst selectivity is poor and the soluble medium is easy to migrate, resulting in high polarization voltage, low efficiency and short service life during discharge/charging.

Method used

Using a ferroelectric photocatalyst layer with directional space charge separation function, it is made into a ferroelectric photocatalyst by calcining bismuth oxide, anatase titanium dioxide, niobium oxide and other materials at high temperature, and combined with conductive carbon and modified binder to form an efficient Ferroelectric photopositive electrode.

Benefits of technology

It improves the energy conversion efficiency and cycle life of lithium air batteries, enhances catalytic activity and stability, inhibits the loss of active materials, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a ferroelectric photopositive electrode based on a lithium-air battery and a preparation method thereof, belonging to the technical field of battery electrodes. The invention prepares a ferroelectric photocatalyst by grinding and mixing bismuth oxide, anatase titanium dioxide, niobium oxide, a eutectic agent and tungsten oxide and then calcining at high temperature, then mixing the ferroelectric photocatalyst, conductive carbon, a binder and an organic solvent to prepare a slurry, and finally spraying the slurry on both sides of a current collector, and obtaining a ferroelectric photopositive electrode based on a lithium-air battery after drying. The ferroelectric photopositive electrode of the invention has a directional spatial charge separation function, and has high photoelectrocatalytic activity, high photogenerated carrier separation efficiency and high physicochemical stability, successfully solving the problems of poor stability and fast carrier recombination efficiency of the existing light-assisted lithium-air battery positive electrode, and the energy conversion efficiency of the light-assisted lithium-air battery can reach up to 95.9% and the service life can reach up to 300 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery electrodes, and in particular, relates to a ferroelectric optical positive electrode based on a lithium-air battery and a preparation method thereof. Background Art

[0002] At present, lithium-ion batteries are close to their theoretical specific energy (387Wh / kg), and even after comprehensive optimization, the chemical limitations of lithium-ion batteries still make it difficult to meet the demand for higher energy density. For this reason, research activities on the next generation of alternative energy storage devices are becoming more and more intensive. Among the many candidate technologies, lithium-air batteries have attracted much attention because of their theoretical specific energy that is 3 to 10 times higher than that of existing commercial lithium-ion batteries (about 3500Wh / kg) and their higher output voltage. Lithium-air batteries have great application prospects, and their current electrochemical performance is still far from expectations. In theory, lithium-air batteries should be able to achieve reversible reduction and release of oxygen during discharge and charge, and the output voltage of the battery depends on the theoretical potential difference between the air positive electrode and the negative electrode. However, in the actual discharge / charge process, the oxygen reduction / precipitation reaction is often accompanied by high overpotential and low round-trip efficiency. Therefore, electrocatalysts or electrolyte additives become necessary means to accelerate the positive electrode reaction. In recent years, people have made important progress in the development of positive electrode electrocatalysts (such as precious metals, metal oxides / sulfides and carbon materials) and soluble redox media (such as lithium halides, tetrahydrofullerene and tetramethylpiperidinyloxy). However, the prior art lacks catalysts that can effectively promote the discharge / charge process and reduce the polarization voltage. The catalysts in the prior art have poor selectivity, and the soluble medium easily migrates to the negative electrode, resulting in aggravated side reactions and shortening the service life of the battery. Therefore, at this stage, there is an urgent need for a catalyst with high catalytic activity and strong selectivity, and at the same time, a binder with stronger curing effect that can prevent the migration of the soluble medium in the catalyst is needed. Summary of the invention

[0003] The object of the present invention is to provide a ferroelectric optical cathode based on a lithium-air battery and a preparation method thereof, so as to solve the problems mentioned in the above background technology.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A ferroelectric photocatalyst cathode based on a lithium-air battery, characterized in that it comprises a current collector and a ferroelectric photocatalyst layer with directional spatial charge separation coated on the surface of the current collector, and the current collector and the ferroelectric photocatalyst layer with directional spatial charge separation coated on the surface of the current collector are tightly bonded by a binder;

[0006] A method for preparing a ferroelectric optical cathode based on a lithium-air battery, characterized in that it comprises the following steps:

[0007] Step 1: Add bismuth oxide, anatase titanium dioxide, niobium oxide, eutectic agent, and tungsten oxide into a mortar and grind and mix thoroughly;

[0008] Step 2: placing the mixture obtained by grinding in the first step in a crucible for high-temperature calcination, then washing the calcined product with deionized water and drying it to constant weight to obtain a ferroelectric photocatalyst;

[0009] Step 3: stirring and mixing the ferroelectric photocatalyst, conductive carbon, binder and organic solvent obtained in the second step to obtain a slurry;

[0010] Step 4: Spray the slurry obtained in the third step onto both sides of the current collector, and after drying, obtain a ferroelectric optical positive electrode based on a lithium-air battery.

[0011] Furthermore, the eutectic agent is prepared by mixing sodium chloride and potassium chloride in a molar ratio of 1:1.

[0012] Furthermore, the conductive carbon is one of conductive polymers, hierarchical porous carbon spherical shells, carbon nanotubes and small particle conductive carbon black.

[0013] Furthermore, the organic solvent is N-methylpyrrolidone.

[0014] Furthermore, the current collector is one of carbon paper, porous carbon nanotube aerogel, and porous graphene aerogel.

[0015] Furthermore, the molar ratio of bismuth oxide, anatase titanium dioxide and niobium oxide used in the first step is 3:2:1, and the mass fraction of tungsten oxide is preferably 3.5%.

[0016] Furthermore, the mass ratio of the ferroelectric photocatalyst, the conductive carbon and the binder used in the third step is 6-8:1-3:1.

[0017] Furthermore, the temperature condition of high temperature calcination in the second step is 700-1000° C., preferably 800° C.; the time condition of high temperature calcination is 1-3 h, preferably 2 h.

[0018] Further, the adhesive is prepared by the following steps:

[0019] Step 1: maleic anhydride, 5-aminoresorcinol, tetrabutylammonium bromide and xylene are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, and the mixture is reacted at 130°C for 8-10 hours. After the reaction is completed, ether is added to the three-necked flask, vacuum filtered, and the obtained solid is recrystallized to obtain intermediate 1;

[0020] Step 2: Mix the intermediate 1, chlorosulfonic acid, triethylamine and chloroform in a three-necked flask, start magnetic stirring, and react at room temperature for 4-6 hours. After the reaction is completed, wash with deionized water, separate the organic layer with a separatory funnel, and then rotary evaporate to obtain the intermediate 2;

[0021] Step 3: Mix polyvinylidene fluoride and sodium hydroxide alcohol solution in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at 70°C for 2-3h. After the reaction is completed, vacuum filter and wash the obtained solid with deionized water to obtain intermediate 3;

[0022] Step 4: Mix intermediate 2, intermediate 3, benzoyl peroxide and tetrahydrofuran in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, react at 70° C. for 12-14 hours, and after the reaction is completed, vacuum filter and recrystallize the obtained solid to obtain the binder;

[0023] Furthermore, the amount ratio of maleic anhydride, 5-aminoresorcinol, tetrabutylammonium bromide and xylene used in step 1 is 0.1 mol: 0.1 mol: 3-4 g: 60-80 mL.

[0024] Furthermore, the usage ratio of the intermediate 1, chlorosulfonic acid, triethylamine and chloroform used in step 2 is 0.07 mol: 0.14-0.18 mol: 0.15-0.2 mol: 80-100 mL.

[0025] Furthermore, the sodium hydroxide alcohol solution used in step 3 is a sodium hydroxide anhydrous ethanol solution with a molar concentration of 1 mol / L, and the amount ratio of the polyvinylidene fluoride to the sodium hydroxide alcohol solution is 5 g:40-50 mL.

[0026] Furthermore, the usage ratio of intermediate 2, intermediate 3, benzoyl peroxide and tetrahydrofuran used in step 4 is 0.01 mol: 4-4.5 g: 0.3-0.5 g: 30-40 mL.

[0027] Beneficial effects of the present invention:

[0028] The present invention prepares a ferroelectric photocatalyst by grinding and mixing bismuth oxide, anatase titanium dioxide, niobium oxide, a eutectic agent and tungsten oxide and then calcining them at high temperature, then stirring and mixing the ferroelectric photocatalyst, conductive carbon, a binder and an organic solvent to prepare a slurry, finally spraying the slurry on both sides of a current collector, and obtaining a ferroelectric photopositive electrode based on a lithium-air battery after drying; a self-made ferroelectric photocatalyst is used in the preparation process of the ferroelectric photopositive electrode of the present invention, and the prepared ferroelectric photopositive electrode has a directional spatial charge separation function, and has high photoelectrocatalytic activity, high photogenerated carrier separation efficiency and high physicochemical stability, and successfully solves the problems of poor stability of the positive electrode and fast carrier recombination efficiency of the existing light-assisted lithium-air battery.

[0029] The invention uses maleic anhydride and 5-aminoresorcinol as raw materials, performs an amidation reaction under the catalytic action of tetrabutylammonium bromide to obtain an intermediate 1 with a rigid structure, then performs an esterification reaction between the intermediate 1 and chlorosulfonic acid under the condition of triethylamine as an acid-binding agent to obtain an intermediate 2 with two sulfonate structures, then uses polyvinylidene fluoride as a raw material, performs an elimination reaction in a hot alkaline environment to obtain an intermediate 3 with a double bond, and finally copolymerizes the double bond of the intermediate 3 with the double bond of the intermediate 2 under the condition of benzoyl peroxide as an initiator to obtain a binder. The conventional lithium battery binder polyvinylidene fluoride is a binder of the present invention. Vinyl fluoride is not sufficient to inhibit the shuttling of active substances in the battery anode. The present invention obtains a binder by modifying polyvinylidene fluoride by alkali treatment and grafting an intermediate 2 having a rigid structure and a sulfate group. The sulfate group in the binder of the present invention can fix the metal ions in the ferroelectric photocatalyst on the positive electrode side through reaction, thereby inhibiting the loss of active materials. In addition, the rigid structure in the binder of the present invention can increase the internal rotation resistance between molecules when embedded in the polymer chain, thereby improving the heat resistance and stability of the binder, so that the binder can still maintain good adhesion at higher temperatures.

[0030] The ferroelectric photocathode based on the lithium-air battery of the present invention has good heat resistance and high energy conversion efficiency. The homemade ferroelectric photocatalyst can improve the photocatalytic activity of the electrode and has long-term and stable effect. It can be used in the field of lithium-air batteries to effectively improve the energy conversion efficiency and cycle life of lithium-air batteries. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0032] A binder comprising the following preparation steps:

[0033] Step 1: 0.1 mol of maleic anhydride, 0.1 mol of 5-aminoresorcinol, 3 g of tetrabutylammonium bromide and 60 g of xylene were mixed in a container, stirred evenly, and reacted at 130° C. for 8 h. After the reaction was completed, ether was added to the container, vacuum filtered, and the obtained solid was recrystallized to obtain intermediate 1;

[0034] Step 2: 0.07 mol of intermediate 1, 0.14 mol of chlorosulfonic acid, 0.15 mol of triethylamine and 80 mL of chloroform were mixed in a container, and after magnetic force was uniformized, the mixture was reacted at room temperature for 4 h. After the reaction was completed, the mixture was washed with deionized water, and after separating the organic layer, the intermediate 2 was obtained by rotary evaporation.

[0035] Step 3: 5 g of polyvinylidene fluoride and 40 mL of 1 mol / L sodium hydroxide alcohol solution were mixed in a container, stirred evenly, and reacted at 70° C. for 2 h. After the reaction was completed, vacuum filtration was performed, and the obtained solid was washed with deionized water to obtain intermediate 3;

[0036] Step 4: 0.01 mol of intermediate 2, 4 g of intermediate 3, 0.3 g of benzoyl peroxide and 30 mL of tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 70° C. for 12 h. After the reaction was completed, vacuum filtration was performed, and the obtained solid was recrystallized to obtain a binder. Example

[0037] A binder comprising the following preparation steps:

[0038] Step 1: 0.1 mol of maleic anhydride, 0.1 mol of 5-aminoresorcinol, 3.5 g of tetrabutylammonium bromide and 70 g of xylene were mixed in a container, stirred evenly, and reacted at 130° C. for 9 h. After the reaction was completed, ether was added to the container, vacuum filtered, and the obtained solid was recrystallized to obtain intermediate 1;

[0039] Step 2: 0.07 mol of intermediate 1, 0.16 mol of chlorosulfonic acid, 0.175 mol of triethylamine and 90 mL of chloroform were mixed in a container, and after magnetic force was uniformized, the mixture was reacted at room temperature for 5 h. After the reaction was completed, the mixture was washed with deionized water, and after separating the organic layer, the intermediate 2 was obtained by rotary evaporation.

[0040] Step 3: 5 g of polyvinylidene fluoride and 45 mL of 1 mol / L sodium hydroxide alcohol solution were mixed in a container, stirred evenly, and reacted at 70° C. for 2.5 h. After the reaction was completed, vacuum filtration was performed, and the obtained solid was washed with deionized water to obtain intermediate 3;

[0041] Step 4: 0.01 mol of intermediate 2, 4.25 g of intermediate 3, 0.4 g of benzoyl peroxide and 35 mL of tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 70° C. for 13 h. After the reaction was completed, vacuum filtration was performed, and the obtained solid was recrystallized to obtain a binder. Example

[0042] A binder comprising the following preparation steps:

[0043] Step 1: 0.1 mol of maleic anhydride, 0.1 mol of 5-aminoresorcinol, 4 g of tetrabutylammonium bromide and 80 g of xylene were mixed in a container, stirred evenly, and reacted at 130° C. for 10 h. After the reaction was completed, ether was added to the container, vacuum filtered, and the obtained solid was recrystallized to obtain intermediate 1;

[0044] Step 2: 0.07 mol of intermediate 1, 0.18 mol of chlorosulfonic acid, 0.2 mol of triethylamine and 100 mL of chloroform were mixed in a container, and after magnetic force was uniformized, the mixture was reacted at room temperature for 6 h. After the reaction was completed, the mixture was washed with deionized water, and after separating the organic layer, the mixture was rotary evaporated to obtain intermediate 2;

[0045] Step 3: 5 g of polyvinylidene fluoride and 50 mL of 1 mol / L sodium hydroxide alcohol solution were mixed in a container, stirred evenly, and reacted at 70° C. for 3 h. After the reaction was completed, vacuum filtration was performed, and the obtained solid was washed with deionized water to obtain intermediate 3;

[0046] Step 4: 0.01 mol of intermediate 2, 4.5 g of intermediate 3, 0.5 g of benzoyl peroxide and 40 mL of tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 70° C. for 14 h. After the reaction was completed, vacuum filtration was performed, and the obtained solid was recrystallized to obtain a binder. Example

[0047] A method for preparing a ferroelectric optical cathode based on a lithium-air battery comprises the following steps:

[0048] Step 1: Mix 0.699 g bismuth oxide, 0.08 g anatase titanium dioxide, 0.133 g niobium oxide, 8 g eutectic and 0.21 g tungsten oxide and grind them in a mortar for 30 min.

[0049] Step 2: placing the mixture obtained by grinding in the first step into an alumina crucible, calcining at 700°C for 1 hour, washing with deionized water and drying to constant weight to obtain a ferroelectric photocatalyst;

[0050] Step 3: Mix the ferroelectric photocatalyst, carbon nanotubes and the binder obtained in Example 1 at a mass ratio of 6:1:1, add N-methylpyrrolidone, and prepare a positive electrode slurry with a concentration of 0.5 mg / mL;

[0051] Step 4: Place the porous carbon nanotube aerogel on a heating table, adjust the temperature to 90°C, spray the slurry obtained in the third step evenly on the surface using an air pump spray gun, and then place it in a vacuum drying oven at 90°C for 10 hours to obtain a ferroelectric optical positive electrode based on a lithium-air battery.

[0052] The eutectic used in the first step is prepared by mixing sodium chloride and potassium chloride in a molar ratio of 1:1. Example

[0053] A method for preparing a ferroelectric optical cathode based on a lithium-air battery comprises the following steps:

[0054] Step 1: Mix 0.699 g bismuth oxide, 0.08 g anatase titanium dioxide, 0.133 g niobium oxide, 8 g eutectic and 0.21 g tungsten oxide and grind them in a mortar for 30 min.

[0055] Step 2: placing the mixture obtained by grinding in the first step into an alumina crucible, calcining at 800°C for 2h, washing with deionized water and drying to constant weight to obtain a ferroelectric photocatalyst;

[0056] Step 3: Mix the ferroelectric photocatalyst, the small particle conductive carbon black and the binder obtained in Example 2 in a mass ratio of 7:2:1, add N-methylpyrrolidone, and prepare a positive electrode slurry with a concentration of 0.5 mg / mL;

[0057] Step 4: Place the carbon paper on a heating table, adjust the temperature to 90°C, spray the slurry obtained in the third step evenly on the surface using an air pump spray gun, and then place it in a vacuum drying oven at 90°C for 10 hours to obtain a ferroelectric optical positive electrode based on a lithium-air battery.

[0058] The eutectic used in the first step is prepared by mixing sodium chloride and potassium chloride in a molar ratio of 1:1. Example

[0059] A method for preparing a ferroelectric optical cathode based on a lithium-air battery comprises the following steps:

[0060] Step 1: Mix 0.699 g bismuth oxide, 0.08 g anatase titanium dioxide, 0.133 g niobium oxide, 8 g eutectic and 0.21 g tungsten oxide and grind them in a mortar for 30 min.

[0061] Step 2: placing the mixture obtained by grinding in the first step into an alumina crucible, calcining at 1000°C for 3h, washing with deionized water and drying to constant weight to obtain a ferroelectric photocatalyst;

[0062] Step 3: Mix the ferroelectric photocatalyst, the hierarchical porous carbon spherical shell and the binder obtained in Example 3 in a mass ratio of 8:3:1, add N-methylpyrrolidone, and prepare a positive electrode slurry with a concentration of 0.5 mg / mL;

[0063] Step 4: Place the porous graphene aerogel on a heating table, adjust the temperature to 90°C, spray the slurry obtained in the third step evenly on the surface using an air pump spray gun, and then place it in a vacuum drying oven at 90°C for 10 hours to obtain a ferroelectric optical positive electrode based on a lithium-air battery.

[0064] The eutectic used in the first step is prepared by mixing sodium chloride and potassium chloride in a molar ratio of 1:1.

[0065] Experimental Example 1

[0066] The ferroelectric photocathode based on lithium-air battery obtained in Example 4-6 is assembled into a light-assisted lithium-air battery: the battery includes a metallic lithium negative electrode, a ferroelectric photocathode based on lithium-air battery, and a glass fiber separator with 1M liquid electrolyte LiTFSI / TEGDME.

[0067] The charge and discharge performance of three groups of light-assisted lithium-air batteries were tested under the following test conditions: xenon light illumination, current density 0.02 mA / cm -2 , the cut-off voltage is 2V-4.5V, the test results are shown in Table 1:

[0068] Table 1

[0069] It can be seen from Table 1 that the lithium-air battery assembled by the ferroelectric photoelectric cathode based on the lithium-air battery of the present invention has a high energy conversion efficiency, which can reach more than 90%, and a long cycle life. Therefore, the ferroelectric photoelectric cathode based on the lithium-air battery of the present invention can be widely used in the field of lithium batteries.

[0070] The above is a detailed introduction to a ferroelectric photopositive electrode based on a lithium-air battery and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combination method. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention can be combined with each other in any way. The reason why these combinations are not exhaustively described in this specification is only for the consideration of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A ferroelectric optical cathode based on a lithium-air battery, characterized in that: It comprises a current collector and a ferroelectric photocatalyst layer with directional spatial charge separation coated on the surface of the current collector, and the current collector and the ferroelectric photocatalyst layer with directional spatial charge separation coated on the surface of the current collector are tightly bonded by a binder; Wherein, the binder is prepared by the following steps: Step 1: maleic anhydride, 5-aminoresorcinol, tetrabutylammonium bromide and xylene are mixed in a container, stirred evenly, and reacted at 130° C. for 8-10 hours to obtain intermediate 1; Step 2: Mix intermediate 1, chlorosulfonic acid, triethylamine and chloroform in a three-necked flask, stir evenly, and react at room temperature for 4-6 hours to obtain intermediate 2; Step 3: Mix polyvinylidene fluoride and sodium hydroxide alcohol solution in a container, stir evenly, and react at 70° C. for 2-3 hours to obtain intermediate 3; Step 4: Mix intermediate 2, intermediate 3, benzoyl peroxide and tetrahydrofuran in a container, stir evenly, and react at 70° C. for 12-14 hours to obtain the binder; A method for preparing a ferroelectric optical cathode based on a lithium-air battery comprises the following steps: Step 1: Add bismuth oxide, anatase titanium dioxide, niobium oxide, eutectic agent and tungsten oxide into a mortar and grind and mix them thoroughly, wherein the molar ratio of bismuth oxide, anatase titanium dioxide and niobium oxide is 3:2:1, and the mass fraction of tungsten oxide is 3.5%; Step 2: placing the mixture obtained by grinding in the first step in a crucible for high-temperature calcination, then washing the calcined product with deionized water and drying it to constant weight to obtain a ferroelectric photocatalyst, wherein the high-temperature calcination temperature condition is 700-1000° C., and the high-temperature calcination time condition is 1-3 hours; Step 3: stirring and mixing the ferroelectric photocatalyst, conductive carbon, binder and organic solvent obtained in the second step to obtain a slurry; Step 4: Spray the slurry obtained in the third step onto both sides of the current collector, and after drying, obtain a ferroelectric optical positive electrode based on a lithium-air battery.

2. A ferroelectric optical cathode based on a lithium-air battery according to claim 1, characterized in that: The amount ratio of maleic anhydride, 5-aminoresorcinol, tetrabutylammonium bromide and xylene used in step 1 is 0.1 mol: 0.1 mol: 3-4 g: 60-80 mL.

3. A ferroelectric optical cathode based on a lithium-air battery according to claim 1, characterized in that: The usage ratio of intermediate 1, chlorosulfonic acid, triethylamine and chloroform used in step 2 is 0.07 mol: 0.14-0.18 mol: 0.15-0.2 mol: 80-100 mL.

4. A ferroelectric optical cathode based on a lithium-air battery according to claim 1, characterized in that: The sodium hydroxide alcohol solution used in step 3 is a sodium hydroxide anhydrous ethanol solution with a molar concentration of 1 mol / L, and the amount ratio of the polyvinylidene fluoride to the sodium hydroxide alcohol solution is 5 g: 40-50 mL.

5. A ferroelectric optical cathode based on a lithium-air battery according to claim 1, characterized in that: The usage ratio of intermediate 2, intermediate 3, benzoyl peroxide and tetrahydrofuran used in step 4 is 0.01 mol: 4-4.5 g: 0.3-0.5 g: 30-40 mL.

6. The method for preparing a ferroelectric optical cathode based on a lithium-air battery according to claim 1, characterized in that: The eutectic is prepared by sodium chloride and potassium chloride in a molar ratio of 1:1, the conductive carbon is one of hierarchical porous carbon spherical shells and carbon nanotubes, the organic solvent is N-methylpyrrolidone, and the current collector is one of carbon paper, porous carbon nanotube aerogel, and porous graphene aerogel.

7. The method for preparing a ferroelectric optical cathode based on a lithium-air battery according to claim 1, characterized in that: The mass ratio of the ferroelectric photocatalyst, conductive carbon and binder used in the third step is 6-8:1-3:

1.

8. The method for preparing a ferroelectric optical cathode based on a lithium-air battery according to claim 1, characterized in that: In the second step, the temperature condition of high temperature calcination is 800°C; the time condition of high temperature calcination is 2h.